Designing Science Center with High-Tech Architecture Approach in Medan City - Edsa, Egi Satri; Abdillah, Wahyu (Komunitas Menulis dan Meneliti (Kolibi), 2024)
The progress of a nation is highly dependent on the quality of its education, both through formal and informal education. Science and Technology (Science and Technology) oriented education has an important role in creating a qualified and competitive next generation. However, the progress of science and technology in Indonesia has not been fully supported by public interest, mainly due to the lack of supporting facilities, especially for students. Therefore, constructing the Science Center in Medan City is proposed as a place for entertainment education. Presenting science and technology in a practical and interactive manner is expected to increase public interest in science and technology, create a technologically responsive generation, and potentially serve as a tourist attraction. The Science Center is expected to shape scientific skills and attitudes at an early age, change the paradigm of consumerism, and encourage science and technology awareness in society.